Karakteristik Habitat Famili Carangidae di Padang Lamun Pesisir Kota Bontang-Indonesia - Irawan, Aditya (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2021)
The association of seagrass beds with river estuaries and other coastal ecosystems provides unique characteristics for the formation of seagrass habitats and the interaction of fish species with seagrass beds. The purpose of the study was to determine the habitat characteristics of the Carangidae family in the coastal seagrass beds of Bontang City. The study was carried out from March to December 2020. Sampling of fish from the Carangidae family was carried out based on the catch of the trap net fishing gear (belat: local name). Seagrass sampling was carried out using the transect method and water quality sampling was carried out in situ. Analysis of habitat characteristics, species of Carangidae used Correspondence Analysis and Pearson Moment Product correlation, spatial distribution characteristics of water quality variables used Principal Component Analysis. Characteristics of seagrass species that make up seagrass beds provide an niche for species of Carangidae in their biological phase.